2021
DOI: 10.1097/rct.0000000000001241
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Computed Tomography Density of Thyroid Gland in Children: A Single-Center Retrospective Study in Northern China

Abstract: Objective:The thyroid gland normally presents as a hyperdense organ on noncontrast computed tomography (CT) in adults. The correlation between thyroid gland CT density and its functional status has been studied; however, little is known regarding its density in children with normal thyroid functions. We aimed to assess the correlation between thyroid gland CT density and age in children with normal thyroid functions.Methods: From April 2017 to March 2021, we enrolled 74 patients who had normal thyroid function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently, the influences of physiological factors such as age, sex and thyroid functional status on CT or DECTderived parameters have been studied increasingly [12][13][14][15]. Yi et al has reported a positive correlation between thyroid CT density and age in children [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the influences of physiological factors such as age, sex and thyroid functional status on CT or DECTderived parameters have been studied increasingly [12][13][14][15]. Yi et al has reported a positive correlation between thyroid CT density and age in children [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the influences of physiological factors such as age, sex and thyroid functional status on CT or DECTderived parameters have been studied increasingly [12][13][14][15]. Yi et al has reported a positive correlation between thyroid CT density and age in children [12]. Meanwhile, Li et al has found that the TIC in TG measured using DECT correlated positively with free triiodothyronine (FT3), but correlated negatively with thyroid-stimulating hormone (TSH), while the mean IC of TG was positively correlated with both FT3 and total triiodothyronine (TT3) in euthyroid patients [15].…”
Section: Introductionmentioning
confidence: 99%